DUS testing in 15 Bread Wheat (Triticum aestivum L.) and Durum Wheat (Triticum durum Desf.) Varieties of Central India - DK VERMA; JB SINGH; RAVINDRA PANWAR (Seed Research, 2026)
Present investigation was carried out at ICAR-Indian Agriculture Research Institute, Regional Station,Indore during Rabi seasons of 2020-21 and 2021-22 to examine the different morphological characters for distinctness, uniformity and stability of durum and bread wheat varieties. Fifteen genotypes were studied over two years and observations on thirty six morphological characters were recorded. The study revealed that morphological characters of wheat plant viz. plant growth habit, coleoptile anthocyanin colouration, flag leaf anthocyanin colouration of auricle, time of ear emergence, ear waxiness, waxiness of peduncle, flag leaf length, peduncle attitude, flag leaf width, plant height, lower glume shoulder width, lower glume shoulder shape, outer glume pubescence, and awns attitude were the most important characters which could easily distinguish the durum wheat varieties. The characters like foliage colour, flag leaf attitude, flag leaf waxiness of sheath, ear length, lower glume beak length, lower glume beak shape, flag leaf waxiness of blade, ear colour, awns colour, are also found useful in distinguishing durum wheat varieties. The seed morphological characteristics such as grain hardness, grain germ width and grain shape are found to be useful in discriminating bread and durum wheat varieties. But some characters like ear density, awn length and 1000 seed weight are not found to be so useful in distinguishing bread and durum wheat varieties in the present investigation. The study also revealed that the characters viz., flag leaf hairs on auricle, brush hairs, peduncle length, ear shape in profile easily distinguished bread wheat variety from rest of the durum wheat varieties. But these characters could not distinguish among durum wheat varieties. The grain colouration with phenol also could not distinguish among durum wheat varieties but it strongly distinguished bread wheat variety from all the durum wheat varieties in the study.